Drivers of income inequality in Ireland and Northern Ireland - Karina Doorley; Michele Gubello; Dora Tuda (The Economic and Social Research Institute (ESRI), 2024)
The distribution of income differs in Ireland and Northern Ireland. Historically, Northern Ireland has been marked by lower levels of income and lower income inequality. The Gini coefficient, a widely used measure of income inequality which increases as income becomes more dispersed, has averaged 0.29 in Northern Ireland and slightly more than this, at 0.31 in Ireland, between 2003 and 2019. Using harmonised microsimulation models for Ireland (SWITCH) and Northern Ireland (UKMOD), we simulate the Gini coefficient to be 0.26 in Northern Ireland and 0.28 in Ireland in 2019, although these point estimates are not statistically different from each other. Nevertheless, as seemingly similar income distributions can come about for different underlying reasons, we analyse the drivers of income inequality in Ireland and Northern Ireland. Previous research has identified marked differences in demographics, working patterns, wage levels and the tax-benefit system between Ireland and Northern Ireland. These factors are important determinants of income distribution and are likely to contribute differently to how income is distributed in the two jurisdictions. Using a decomposition technique (following Bargain and Callan (2010); Doorley et al. (2021) and Sologon et al. (2021)), this research identifies the drivers of income inequality in Ireland and Northern Ireland in the year 2019. We isolate the relative contributions of market income differences - attributable to demographics, labour market participation and wage levels - and the tax-benefit system to differences in income distribution in the two jurisdictions. We find that differences in inequality in market, or pre-tax and transfer income, are driven by two counteracting forces. On the one hand, the younger and more highly educated population of Ireland results in relatively lower income inequality as there are relatively fewer people with no earnings. On the other hand, the higher and more unequal wages paid to workers in Ireland result in relatively higher market income inequality, all else equal. We estimate that differences in the tax-benefit system also influence the distribution of income in Ireland and Northern Ireland. The Irish tax system is more progressive and reduces income inequality more than the Northern Irish tax system. However, the level and coverage of means-tested benefits in Ireland is lower than that in Northern Ireland. Therefore the Irish means-tested benefit system is inequality-increasing compared to the Northern Irish means-tested benefit system. The combination of these two opposing effects results in similar overall levels of redistribution by the Irish and Northern Irish tax-benefit systems taken as a whole. This research sheds light on possible future developments in income inequality on the island of Ireland. Secular trends in population aging and upskilling are likely to affect the distribution of pre-tax and transfer income in both Ireland and Northern Ireland. The latter is likely to be particularly important in Northern Ireland, where baseline levels of education are lower. This research also finds that, if there is any convergence in the future between the tax-benefit systems of Ireland and Northern Ireland, in the context of increased economic co-operation on the island of Ireland, there may be a limited impact on income inequality due to opposing forces in the tax and benefit system. An understanding of these forces and their impact on income inequality - in isolation and together - can help to guide any such move towards future co-operation.
Keywords: 330